Asia's cauldron the South China Sea and the end of a stable Pacific - Kaplan, Robert D. 1952- (Random House, 2014)
"An examination of the future role of the South China sea in international relations and a tour of the the nations surrounding the South China Sea and their interests in the region. In exploring each of these countries individually, Kaplan clearly shows where the conflicts may arise and why they will be challenging for the international community"--